Changes in society during and after the Industrial Revolution in Great Britain - Kišantal, Jozef (Univerzita Pardubice, 2009)
The Industrial Revolution has been one of the most important moments not only British but also European history. This work concentrates on this period and everything related to it. It deals in detail with the epoch immediately preceding the Revolution, the first half of the 18 th century. If focuses on causes of economic boom and personalities of ruling and politic representation in those days. It tries to look at the industrial growth, geographical changes, social changes and the development of large-scale production to the prejudice of craftsmen including the examples of significant inventors of new machines. The constituent part of the work is devoted to work and life conditions of workers including small children. It seeks to describe the circumstances preceding and following both the French Revolution and the Parliamentary Revolution related to the rise of movement struggling for improvement of social life of people being forgot in previous years. The conclusion of the work tries to summarize the most significant consequences of the Industrial Revolution.
Změny ve společnosti během a po průmyslové revoluci ve Velké Británii
Keywords: Velká Británie; průmyslová revoluce; společnost; Great Britain; Industrial Revolution; society